Corrosion Behaviour of Mild Steel in Acidic Medium in Presence of Aqueous Extract of Allamanda Blanchetii - B. Anand; V. Balasubramanian (E-Journal of Chemistry)
The inhibition efficiency (IE) of an aqueous extract of Allamanda blanchetii (Purple) in controlling corrosion of mild steel which has been evaluated by weight loss method in the absence and presence of corrosion inhibitor at different time intervals at room temperature. The result showed that the corrosion inhibition efficiency of Allamanda blanchetii was found to vary with different time interval and different acid concentrations. Also, it was found that the corrosion inhibition behavior of Allamanda blanchetii is greater in sulphuric acid than citric acid medium. So Allamanda blanchetti can be used as a good inhibitor for preventing mild steel material. The surface analysis study confirms the corrosion of the mild steel and its inhibition by the inhibitor Allamanda blanchetii.